2011
DOI: 10.1146/annurev-fluid-122109-160753
|View full text |Cite
|
Sign up to set email alerts
|

High–Reynolds Number Wall Turbulence

Abstract: We review wall-bounded turbulent flows, particularly high-Reynolds number, zero-pressure gradient boundary layers, and fully developed pipe and channel flows. It is apparent that the approach to an asymptotically high-Reynolds number state is slow, but at a sufficiently high Reynolds number the log law remains a fundamental part of the mean flow description. With regard to the coherent motions, very-large-scale motions or superstructures exist at all Reynolds numbers, but they become increasingly important wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
611
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 811 publications
(651 citation statements)
references
References 138 publications
(173 reference statements)
34
611
2
4
Order By: Relevance
“…On the assumption that the trapezoidal area is maintained, the change with the Reynolds number leads to the blue region in figure 15 changing to the red area, subject to λ min (y) remaining invariant. The consequence is then an increase in the plateau of u ′ u ′ and an extension of the logarithmic decline in u ′ u ′ , as observed by Smits et al 27 , Hultmark et al within the interval 2800 ≤ t + ≤ 3150. It is emphasized here that this is done merely in order to add support to the validity of the relationship between the plateau in the trapezoidal area in figure 14 and the logarithmic decline of u ′ u ′ + (y + ) in the meso-layer.…”
Section: B the Regime Of Attached Eddiesmentioning
confidence: 55%
“…On the assumption that the trapezoidal area is maintained, the change with the Reynolds number leads to the blue region in figure 15 changing to the red area, subject to λ min (y) remaining invariant. The consequence is then an increase in the plateau of u ′ u ′ and an extension of the logarithmic decline in u ′ u ′ , as observed by Smits et al 27 , Hultmark et al within the interval 2800 ≤ t + ≤ 3150. It is emphasized here that this is done merely in order to add support to the validity of the relationship between the plateau in the trapezoidal area in figure 14 and the logarithmic decline of u ′ u ′ + (y + ) in the meso-layer.…”
Section: B the Regime Of Attached Eddiesmentioning
confidence: 55%
“…Many recent experimental results have suggested that the trend towards high Reynolds numbers could reveal some fundamentally different mechanisms at work in the dynamics of highReynolds-number boundary layers compared with their lower-Reynolds-number counterparts (see the reviews by Jiménez [53] and Smits et al [54]). Hutchins & Marusic [55] emphasized the occurrence of large structures whose size can reach up to 15 boundary layer thicknesses long.…”
Section: Further Discussion On Remaining Challenges and Closing Remarksmentioning
confidence: 99%
“…This conjecture is consistent with the behaviour of the single-point turbulent kinetic energy source, s = − uv (dU/dy) − , which is displayed for three Reynolds numbers, Re τ = 550, Re τ = 950 and Re τ = 2000, in figure 4. From the plots the increasing share of the overlap layer to the total single-point energy source is apparent; see Smits, McKeon & Marusic (2011) for a review of the topic.…”
Section: Scale Energy and Scale-energy Sourcementioning
confidence: 99%